VIOLÊNCIA SEXUAL, INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS E GRAVIDEZ: RETROSPECTIVA DE DEZ ANOS EM SERVIÇO DE REFERÊNCIA EM VITÓRIA, ESPÍRITO SANTO, BRASIL. - Souza, Chiara Musso Ribeiro de Oliveira (2022)
Introduction: Sexually transmitted infections (STI) and pregnancy can be consequences of sexual violence. In Brazil, around 50% of women victims of sexual violence do not undergo STI prophylaxis or emergency contraception. Objectives: To describe the demographic, behavioral and clinical aspects of adolescent and adult women in situations of sexual violence, assisted at a reference clinic in Vitoria, ES, over a one decade period. Patients and Methods: This 10-year retrospective cohort study (2010-2019) describes the socio-demographic and epidemiological profile, and frequencies of clinical procedures, STI, pregnancy and legal abortion in 915 women assisted in a sexual violence assistance center in Brazil. Results: A total of 93.29% (842/915) were resident in the Metropolitan Area of the capital, brown-skinned and white 80.83% (733/915); 42.40% (388/915) were adolescents (12-17 years old), 80.44% (736/915) were single, most had no children, average of 1.8 (± 1,0 DP) children. About one-third (313/915) had not had previous sexual intercourse,1.60% (10/653) were pregnant. Rape predominated with 92% (841/915), of which 51.48% (471/915) involved a known or related aggressor, mostly an acquaintance, followed by stepfather or father. Recurrent cases were 24% (227/915). Clinical procedures: 42.62% (390/915) were attended within 72 hours; received STI prophylaxis 43.36% (392/904), emergency contraception 38.60% (394/904), blood collection 71.57% (647/904). Prevalence: syphilis 0.32% (2/653), hepatitis B 0.16% (1/653), pregnancy 1.60% (10/653). Incidences: syphilis 1.10% (7/663), hepatitis B 0.78% (5/633), hepatitis C 0.64% (4/633), pregnancy 27.17% (172/633). There were no HIV cases. Trichomoniasis 1.9% (2/108), HPV-induced cytological lesions 4.7% (5/108) and bacterial vaginosis 20% (21/108) were found on cervicovaginal samples. There were 129 legal abortions. Conclusions: The sociodemographic aspects and characteristics of aggressions in the studied population are similar to those described in Brazilian national database, including the remarkable number of adolescents, which brings reflections on early sexualization, rape culture, and adult victims’ invisibility. Both STI prophylaxis and emergency contraception were performed in less than half of the women. The frequencies of STI were low, associated with three or more aggressors, number of sexual partners and the age of coitarche. The incidence of pregnancy was high, associated with firearm use and age group, and protected by STI prophylaxis. The frequency of legal abortion was higher than national data. Public policies ensuring access to sexual and reproductive health rights and strategies to improve the quality of care for women in sexual violence situations as well education improvement may decrease vulnerability to STI and unintended pregnancies.